RESPON PERBANKAN SYARI’AH DAN LEMBAGA KEUANGAN SYARIAH DI PAMEKASAN TERHADAP PEMBUKAAN PROGRAM STUDI PERBANKAN SYARI’AH DI STAIN PAMEKASAN - Rudy Haryanto (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
There are three focuses becoming study in this research that is: a) Response ( appresiation ) Syari'ah Bangking and Financial Institution of Syari'ah in Pamekasan, b) Expectation of Syari'ah Bangking and Financial Institution of Syari'Ah in Pamekasan to grad, c) Elementary compentence which must be had by grad. This research uses the approach qualitative trying to watch closely the response of the head Syari'ah Bangking and Financial Institution of Moslem law in Pamekasan to opening of Study Program of Syari’ah Banking in STAIN Pamekasan. Result of this research showing that: Response of Financial Institution and Syari’ah Banking in Pamekasan to opening the Study Program of Syari’ah Banking in STAIN Pamekasan is very good, and they are also ready for cooperating in powering the Study Program of Syari’ah Banking in STAIN Pamekasan. Expectation of Syari’ah Banking and Financial Institution of Syari'ah in Pamekasan to grad of Study Program of Syari’ah Banking in STAIN Pamekasan, that is; the grad of Study Program of Syari’ah Banking STAIN Pamekasan next, absolute mastering the conception of Syari’ah Banking supported with knowledge of conventional banking concept and domination of information Technology Skill. Elementary compentence which must be had by the grad of Study Program of Syari’ah Banking in STAIN Pamekasan, that is; some of responders assess is competent, and some of other assess still many conventional banking payload, less payload of syari’ah banking, and still less subjects which uplift the skill and practice because the next grad have to ready to work in banking area.